Sensitivity and Specificity Comparison Between APFEL, KOIVURANTA, and SINCLAIR Score As PONV Predictor In Post General Anesthesia Patient - M Yusuf Gunawan; Arie Utariani; Maulydia Maulydia; Anna Surgean Veterini (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTBackground: Post Operative Nausea Vomiting (PONV) are the two most common and unpleasant side effects after anesthesia and surgery. Without proper prophylactic administration, the PONV incidence is currently around 20% -30% in normal patients and 70% in high-risk patients (Butterworth et al., 2013). Recently, many PONV predictor scores have been used to determine the PONV severity and prophylactic administration. Objective: To compare the scores of Apfel, Koivuranta, and Sinclair as predictors of PONV in adult patients after general anesthesia at RSUD Dr. Soetomo. Methods: A cross-sectional study design conducted in 100 patients who underwent elective surgery under general anesthesia at RSUD Dr. Soetomo Surabaya. Patients who meet the criteria will be recorded in the clinical research form and being followed to evaluate the assessment using Apfel, Koivuranta, and Sinclair scores when the patient is in the recovery room and the ward. A diagnostic test is performed to assess the accuracy between these scores. Results: In this study, the prevalence of PONV after general anesthesia in elective surgery at GBPT RSUD Dr Soetomo Surabaya is 26%. The Apfel score obtained has a sensitivity value of 79.5%, a specificity of 45.9% with an AUC value of 0.701. The Koivuranta score has a sensitivity value of 96.2%, a specificity of 27% with an AUC value of 0.628. The Sinclair score has a sensitivity value of 73.1%, a specificity of 48.6% with an AUC value of 0.619. Conclusion: Apfel's score is more accurate PONV prediction score and has a simpler score determination variable. Keywords                   : PONV, predictor score, apfel score, koivuranta score, sinclair score, general anesthesia.